A Common Law Theory of Judicial Review The Living Tree - Waluchow, W. J (Cambridge University Press, 2013)
In the early 1980s Canada experienced a fundamental change in its political and legal structures.AnewConstitution Act (1982) came into effect, declaring itself to be “the supreme law of Canada.” This new Constitution Act further decreed that “any law that is inconsistent with [its] provisions . . . is, to the extent of the inconsistency, of no force or effect.”1 In themselves, these statements seem innocuous enough. By its very nature a constitution contains a society’s basic law; it is reasonable, therefore, to think that it trumps any subordinate law with which it conflicts. What made the Constitution Act’s declarations so momentous and deeply controversial, however, was the inclusion of a new Charter of Rights and Freedoms. This specified a number of abstract rights of political morality that federal, provincial, and municipal governments were legally barred from infringing.2 Among these rights were the right to equality before and under the law; the right to life, liberty, and security of the person, coupled with the companion right not to be deprived of the former except in accordance with the principles of fundamental justice; and the right to freedom of thought, belief, opinion, expression, and association.3